2018
DOI: 10.3390/genes9030141
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Coding Regulatory RNA Revolution in Archaea

Abstract: Small non-coding RNAs (sRNAs) are ubiquitously found in the three domains of life playing large-scale roles in gene regulation, transposable element silencing and defense against foreign elements. While a substantial body of experimental work has been done to uncover function of sRNAs in Bacteria and Eukarya, the functional roles of sRNAs in Archaea are still poorly understood. Recently, high throughput studies using RNA-sequencing revealed that sRNAs are broadly expressed in the Archaea, comprising thousands … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 52 publications
2
41
0
1
Order By: Relevance
“…This novel finding is representative of published work in model organisms, where a wide range of sRNAs has been found so far in prokaryotes, from less than a dozen to more than a thousand per genome (see Fig. S7 in the supplemental material) (1,5).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This novel finding is representative of published work in model organisms, where a wide range of sRNAs has been found so far in prokaryotes, from less than a dozen to more than a thousand per genome (see Fig. S7 in the supplemental material) (1,5).…”
Section: Discussionsupporting
confidence: 77%
“…The roles of regulatory sRNAs have been extensively studied in Bacteria and, to a lesser extent, in archaeal model systems (1,5), but to date, only four studies have reported the discovery of sRNAs in microbial communities. In one study, Shi et al (6) used metatranscriptomic data to identify unique microbial intergenic sRNAs in the ocean's water column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they do not overlap their target genes or bind their targets mRNAs with 429 perfect complementary, which make finding targets for these sRNAs very challenging 430 without genetic tools (Gelsinger and DiRuggiero 2018b). 431…”
Section: Gelsinger and Diruggiero 2018b) 389mentioning
confidence: 99%
“…An RNA that cannot encode a protein is known as a noncoding RNA (ncRNA) 6 . With the development of high‐throughput sequencing technology, the biological functions of the ncRNAs have been discovered gradually, 7,8 and dysfunction of ncRNAs can lead to the occurrence of many kinds of neoplasms, including HCC 9,10 . Some microRNAs are critical regulators in the development of HCC and are involved in the processes of proliferation, differentiation, metastasis, infiltration, apoptosis, and metabolism 11 …”
Section: Introductionmentioning
confidence: 99%